2013
DOI: 10.1080/15567036.2010.518217
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Polyacrylonitrile Fiber/Binary of Fatty Acids Composites as Phase Change Materials

Abstract: A new kind of form-stable polyacrylonitrile fiber/binary of fatty acids composites as phase change materials was prepared by a solution blending process. In this material, the binary system between stearic acid and lauric acid with different components was served as latent heat storage material and polyacrylonitrile as the supporting material, N,N-dimethylformamide as solvent. Phase change temperature and latent heat and the thermal stability of the polyacrylonitrile/binary of fatty acids composites were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…It can be seen from Fig. 5a, the LA shows obvious crystalline cross-extinction patterns (also reported in previous research 25,26 ), which is different from that of PEG reported in previous study. 27 Seen from Fig.…”
Section: Crystalline Propertiescontrasting
confidence: 67%
“…It can be seen from Fig. 5a, the LA shows obvious crystalline cross-extinction patterns (also reported in previous research 25,26 ), which is different from that of PEG reported in previous study. 27 Seen from Fig.…”
Section: Crystalline Propertiescontrasting
confidence: 67%
“…It has attracted more and more researchers to explore the PAN as PCM packaging material in recent years [25][26][27][28]. Here, we prepare a novel cross-linked network structure of acrylonitrile copolymer P(AN-co-IA) with itaconic acid (IA) as comonomer.…”
Section: Introductionmentioning
confidence: 98%
“…In order to solve these problems, the shape-stabilized PCMs, which are prepared by incorporating solid-liquid PCMs into supporting materials through encapsulation or impregnation, emerged. The shape-stabilized PCMs based on organic PCMs, including paraffin [7,8], fatty acids [9][10][11] and poly (ethylene glycol) (PEG) [12,13] have been extensively studied owing to the fact that they have suitable energy storage density, no corrosivity and no subcooling. Nevertheless, the inorganic PCMs, especially the hydrated salts, are rarely reported to be prepared into shape-stabilized PCMs, although they enjoy the advantages of high storage density, high thermal conductivity and low cost.…”
Section: Introductionmentioning
confidence: 99%